2009
DOI: 10.1128/jvi.00382-09
|View full text |Cite
|
Sign up to set email alerts
|

Negative Autoregulation of Epstein-Barr Virus (EBV) Replicative Gene Expression by EBV SM Protein

Abstract: The Epstein-Barr virus (EBV) SM protein is essential for lytic EBV DNA replication and virion production. When EBV replication is induced in cells infected with an SM-deleted recombinant EBV, approximately 50% of EBV genes are expressed inefficiently. When EBV replication is rescued by transfection of SM, SM enhances expression of these genes by direct and indirect mechanisms. While expression of most EBV genes is either unaffected or enhanced by SM, expression of several genes is decreased in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…The RNA in those studies was detected by a sensitive RNase protection assay, and it was unclear whether IP of SM from EBV-infected cells would yield associated RNA in amounts adequate to be analyzed by qRT-PCR for all EBV transcripts. We therefore utilized a cell line derived from the Burkitt lymphoma cell line, P3HR1, that was engineered to permit efficient, high-level lytic EBV replication and gene expression (45). The P3HR1-ZHT cell line contains a stably transfected chimeric gene consisting of the Z immediate-early transactivator fused to a 4-HT-specific hormone binding domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA in those studies was detected by a sensitive RNase protection assay, and it was unclear whether IP of SM from EBV-infected cells would yield associated RNA in amounts adequate to be analyzed by qRT-PCR for all EBV transcripts. We therefore utilized a cell line derived from the Burkitt lymphoma cell line, P3HR1, that was engineered to permit efficient, high-level lytic EBV replication and gene expression (45). The P3HR1-ZHT cell line contains a stably transfected chimeric gene consisting of the Z immediate-early transactivator fused to a 4-HT-specific hormone binding domain.…”
Section: Resultsmentioning
confidence: 99%
“…P3HR1 is a Burkitt lymphoma cell line infected with EBV type 2 (31), and B95-8 is a marmoset B-cell line transformed by EBV type 1 (26). Both cell lines were transfected and selected to stably express a fusion protein containing the BZLF1 transactivator of early lytic cycle replication fused to the hormone domain of the estrogen receptor, which, in the presence of 4-hydroxytamoxifen (4-HT), allows the functional release of BZLF1, inducing lytic EBV replication (19,45). The P3HR1-ZHT and B958-ZHT cell lines were propagated in RPMI supplemented with 10% fetal bovine serum (HyCLone), 0.8 mg/ml G418 (AG Scientific), and GlutaMax (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…HEK293 cells stably carrying an ORF59-GFP fusion gene that also inducibly expresses SM-dependent GFP were maintained as previously described (8). P3HR1-ZHT is an EBV-positive lymphoma cell line that contains the EBV BZLF1 gene fused to the hormone-binding domain of the 4-hydroxytamoxifen (4HT) receptor that allows robust induction of EBV replication with 4HT treatment (30). The gastric carcinoma cell line AGS was infected with GFP-expressing EBV Akata BX1 (31).…”
Section: Methodsmentioning
confidence: 99%
“…We and others have previously shown that SM plays multiple roles in posttranscriptional processing of EBV mRNA and cellular mRNA (2,9,17,18,23,31,35,39,40). Although the target sequences for SM binding have not been biochemically defined, abundant evidence indicates that SM contacts RNA directly.…”
Section: Discussionmentioning
confidence: 99%
“…SM has multiple functions in enhancing EBV gene expression posttranscriptionally, binds target gene mRNA, enhances nuclear mRNA export and stability, and modulates cellular and EBV RNA splicing (2,9,17,18,23,31,35,39,40). SM is essential for EBV replication and EBV recombinants with insertional deletion of the SM gene are defective for virus production (12).…”
mentioning
confidence: 99%